Basics of Foreign Language Teaching in Inclusive Education in Institutions - Toshmurodova Mukhabbat Nazaralievna (Journal of Higher Education and Academic Advancement, 2024)
Teaching foreign languages in inclusive education in higher education institutions, is becoming one of the most pressing issues of today. An inclusive education system is being introduced in the system of non-philological educational institutions in order to introduce inclusive education. At present, the level of development of students' knowledge in the Republic, the opportunities, features and special attention to the teaching of foreign languages is developing day by day.